Studi Penciptaan Karya Seni Instalasi Berbasis Eksperimen Kreatif Dengan Medium Gembreng - Cholis, Henri (Institut Seni Indoensia Surakarta, 2013)
This research is a study of the creation of installation art based experimentation byexploring new possibilities to craft products that exist in the market gembreng KabanganLaweyan Surakarta as one of the aesthetic elements of installation art , in the form ofreadymade as well as new forms that can be developed through the technique ofcontrolled by craftsmen gembreng Kabangan Market Surakarta.The object to be observed in this study is the result of the creation of products that havebeen produced and the techniques of making craft products available in the marketKabangan . It is important to seek the possibility of developing various forms as anaesthetic element of the planned installation art .To increase the validity and quality of the work wear means of